2011
DOI: 10.1164/rccm.201012-2082oc
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Air Pollution and Cardiorespiratory Disease in the California Teachers Study Cohort

Abstract: Rationale: Several studies have linked long-term exposure to particulate air pollution with increased cardiopulmonary mortality; only two have also examined incident circulatory disease. Objectives: To examine associations of individualized long-term exposures to particulate and gaseous air pollution with incident myocardial infarction and stroke, as well as all-cause and causespecific mortality. Methods: We estimated long-term residential air pollution exposure for more than 100,000 participants in the Califo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
256
6
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(283 citation statements)
references
References 25 publications
19
256
6
2
Order By: Relevance
“…A further study by Jerrett et al (2009) using the same cohort found unstable risk estimates for ozone and all-cause, cardiopulmonary and cardiovascular mortality, with only respiratory mortality being associated with ozone after adjustment for PM 2.5 . For a more detailed discussion of these and other recent cohort studies (Smith et al, 2009;Zanobetti and Schwartz, 2011;Lipsett et al, 2011) than space here permits, the reader is referred to the REVIHAAP report.…”
Section: Healthmentioning
confidence: 99%
“…A further study by Jerrett et al (2009) using the same cohort found unstable risk estimates for ozone and all-cause, cardiopulmonary and cardiovascular mortality, with only respiratory mortality being associated with ozone after adjustment for PM 2.5 . For a more detailed discussion of these and other recent cohort studies (Smith et al, 2009;Zanobetti and Schwartz, 2011;Lipsett et al, 2011) than space here permits, the reader is referred to the REVIHAAP report.…”
Section: Healthmentioning
confidence: 99%
“…We identified 17 cohort studies Beeson et al 1998;Cao et al 2011;Carey et al 2013;Cesaroni et al 2013;Hales et al 2012;Hart et al 2011;Heinrich et al 2013;Jerrett et al 2013;Katanoda et al 2011;Krewski et al 2009;Lepeule et al 2012;Lipsett et al 2011;McDonnell et al 2000;Naess et al 2007;Pope et al 2002;Raaschou-Nielsen et al 2013) and one case-control study (Hystad et al 2013) of lung cancer that provided estimates of the quantitative relationships between the risk of lung cancer and exposure to PM 2.5 or PM 10 that could be expressed per 10-μg/m 3 change in PM. Estimates from one cohort study (Naess et al 2007) could not be converted to units of 10-μg/m 3 , and thus, this study did not contribute to the meta-estimates.…”
Section: Studies Includedmentioning
confidence: 99%
“…Carbonaceous aerosol contributes to global warming, and black carbon is considered as the second most important agent of global warming after CO 2 (Probert and Tarrant, 1989;Robock and Graf, 1994;Galdos et al, 2013). Recent epidemiologic studies, have displayed the risks of exposure to increased levels of carbonaceous aerosols, revealing notable associations with cardiovascular mortality and morbidity (Ostro et al, 2010;Lipsett et al, 2011;Krall et al, 2013).…”
Section: Introductionmentioning
confidence: 99%